Pediatric oral vitiligo : case report and literature review = Vitiligo oral pediátrico : reporte de caso y revisión de la literatura. - Sharma, Manu
Vitiligo is an acquired hypomelanotic disorder of the skin resulting from loss of functional melanoctyes and it affects approximately 0.5-1% of individuals. 25% of vitiligo in children are diagnosed before 10 years of age. The age of onset of vitiligo in children ranges between 4 to 8 years. Depigmentation in oral cavity can be easily noted and awareness about the condition can be created if they are not aware about vitiligo elsewhere in their body and can be guided for the treatment.